Ensinando ciências em turmas “multisseriadas”: investigando o ensino de saúde no Projeto Segundo Tempo - Moura, Tiago Fernando Alves de [UNESP]; Bidutti, Ana Beatriz Remondi [UNESP]; Gomes, Paulo César [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main objective of this study was to investigate the conduct of a short course on human health. This was planned and taught by a graduate student in the course of Biomedicine and aimed at students enrolled in a public school. The methodology used included the recording of audio interviews and recording on videotape the lessons taught. Classes were taught in eight meetings for students aged between six and ten years old in multigrade classes, i.e., grouped without the criterion of age / grade. The results show a change in the conduct of classes in the graduate student and organization of teaching sequences by the participant and , as a result, increase in oral participation of students and during the activities performed in the classroom.

O principal objetivo do presente trabalho foi mapear a condução de um minicurso sobre a temática ciências e saúde, planejado e ministrado por uma graduanda do curso de Biomedicina e direcionado a alunos matriculados em uma escola pública e participante do projeto Segundo Tempo do Governo Federal. A metodologia utilizada contou com a gravação de entrevistas em áudio e registro em videoteipe das aulas ministradas. Foram ministrados aulas em oito encontros para alunos com faixa etária entre seis e dez anos de idade em turmas multisseriadas, isto é, agrupadas sem o critério de idade/série. Os resultados evidenciam uma modificação na condução das aulas pela graduanda e na organização das sequências de ensino pela participante e, em decorrência disso, aumento na participação oral dos alunos e durante as atividades executadas em sala de aula.
Keywords: Science education; Health education; Primary school; Ensino de ciências; Ensino de saúde; Anos iniciais do ensino fundamental